(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2026)
This article discusses the scientific and methodological foundations of developing an automated software system for digitizing and managing the process of converting agricultural land to other land categories. The issues of reducing the impact of the human factor, increasing transparency, and ensuring the efficient use of land resources by automating the stages of documentation, assessment, monitoring, and decision-making in the land conversion process are considered.